Differences between the antibiotic prescribing pattern of newly arrived refugees in Germany and the German population - Kahl, Fabian; Kühlein, Thomas (Conflict and Health, 2018)
The number of refugees arriving in Europe increased dramatically in 2015, challenging the German health system. Amongst others, the treatment of infectious diseases is an important topic in refugee healthcare. A high prevalence of multi-drug-resistant organisms has been identified among the refugee population. Still, little is known about the prescription of antibiotic medication for refugees. We conducted a descriptive analysis of all antibiotics prescribed to newly arrived refugees who were treated as outpatients between 10/01/2014 and 09/30/2015 in Erlangen, an average sized German town. The City's invoicing documents were used to collect data on prescriptions written for refugees. Basic penicillins, aminopenicillins with beta-lactamase inhibitor and cephalosporins constituted the largest proportion of antibiotics prescribed in the adult refugee group. Of these, both aminopenicillins with beta-lactamase-inhibitor as well as basic penicillins were prescribed significantly more often compared to non-refugees. We conclude that the high percentage of prescriptions of aminopenicillins with beta-lactamase inhibitor is striking and should be further investigated.
EVALuna2:33552